Can Digital Culture Play a Role as A Moderating Variable on The Effect of Transformative Leadership Style on Employee Performance? - Putri Ayu Permata Devi; Hugo Prasetyo Winotoatmojo; Asmita Wulansari Dg. Liwang; Desi Ulpa Anggraini; Fitri Devi Lestari Izaak (Yayasan Inovasi Kemajuan Intelektual, 2025)
This study investigates the complex dynamic between leadership, technology, and human capital by examining whether digital culture acts as a moderating variable in the relationship between transformative leadership style and employee performance. In the rapidly evolving business landscape of 2026, traditional leadership models are being challenged by the necessity of digital integration. This research employs a quantitative approach to analyze how leaders who inspire and intellectually stimulate their subordinates can achieve higher performance outcomes when supported by a robust digital organizational culture. The abstract highlights that while transformative leadership is a strong predictor of performance, the strength of this relationship is contingent on employees' adaptation to digital values, norms, and tools. The findings aim to provide a strategic framework for organizations to synchronize leadership development with cultural digital transformation to optimize workforce productivity.